Non-dirt house floor and the stimulant of environmental health decreased the risk Acute Respiratory Infection (ARI) (Medical Journal of Indonesia, 2006)
The risk factors related to acute respiratory infection (ARI), among others, is house floor. The aim of this research was to identify the influence of the Family Health and Nutrition program (FHN) and other risk factors related to ARI. Data was obtained from a survey conducted in 5 provinces in Indonesia, which received the project of Family Health and Nutrition (FHN) in 2003. The number of subjects was 1,500 families, selected by stratified random sampling method. The questionnaire completion and the observation were done on the spot in the subjectâs house by special trained interviewers. The use of non-dirt house floor built prior to the project of FHN decreased the risk of ARI cases of 51% than the use of dirt house floor [Odds Ratio (OR) = 0.49; 95% Confidence Interval (CI) = 0.25-0.96]. The risk of ARI decreased of 52% among those who received than those which never received the stimulant of environmental health Family Health and Nutrition program (OR = 0.48; 95% CI =0.33-0.70). To decrease the risks of ARI cases, the program of environmental health is necessarily continued. (Med J Indones 2006; 15:60-5)Keywords: ARI, non-dirt house floor, and stimulant of environmental health